Autism spectrum disorder symptoms from ages 2 to 19 years: Implications for diagnosing adolescents and young adults. Issue 1 (12th August 2018) - Bal, Vanessa H.; Kim, So‐Hyun; Fok, Megan; Lord, Catherine
Abstract : This study explored change in social‐communicative symptoms in 140 individuals with childhood autism spectrum disorder (ASD) diagnoses. Trajectories of caregiver‐reported social‐communicative symptoms were examined for three groups (verbal, delayed speech, minimally verbal) from ages 2 to 19 years. Groups showed comparable levels of social‐communicative impairment at 2 years and significant decreases in overall symptom levels across the 17‐year period ( P < .001). Across three subdomains, main effects of time and language ( P < .001) reflected patterns of overall improvement, although children with more impaired language tended to have more caregiver‐reported symptoms relative to verbal peers. A significant time‐by‐language interaction ( P < .001) reflected that trajectories of socioemotional reciprocity symptoms differed according to patterns of language development. In contrast, improvements in the nonverbal communication domain were seen across language groups, whereas deficits in the development and maintenance of relationships improved for only verbal children. Verbal adults showed significant reductions in the prevalence of kseveral symptoms exhibited during childhood. Improvements suggest that symptoms indicative of ASD in young children may no longer be diagnostic markers in adolescents and adults. Relative stability of several items suggests that impaired facial expression may be a core ASD symptom that warrants more systematic study across the lifespan. Research investigating the manifestation of ASD in older individuals is needed to foster development of appropriate assessment tools and interventions. Differential relationships to developmental factors within the broader social‐communication domain underscores a need to focus on more narrowly defined symptom constructs when exploring links between pathophysiology and observable phenotypes. Autism Research 2019, 12: 89–99 . © 2018 International Society for Autism Research, Wiley Periodicals, Inc. Lay Summary: In a sample of 140 participants with autism spectrum disorder (ASD) followed from 2 to 19 years old, this study found that overall social‐communicative symptoms improve across childhood and adolescence. However, timing and amount of change varied for different symptom categories and participants with different language abilities. Findings suggest that some older adolescents and adults with ASD may not exhibit the same difficulties observed in young children with ASD. More research is needed to better understand the strengths and needs of young adults with ASD.